Wada Testing in Pediatric Patients by Use of Propofol Anesthesia - Masters, Lynette T.; Perrine, Kenneth; Devinsky, Orrin; Nelson, Peter Kim (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Wada testing may provide important information for surgical planning in pediatric patients with medically refractory epilepsy, but it is often not used because of the difficulties in performing the angiographic portion of the procedure in conscious children. We reviewed our experience using propofol, a short-acting IV administered anesthetic agent, for pediatric patients undergoing Wada testing.METHODS: In a retrospective review of Wada tests performed on patients younger than 18 years, we identified 24 cases in which propofol anesthesia was used. We reviewed the medical records of these patients, with particular reference to dose of propofol, physiological parameters during anesthesia, and adequacy of neuropsychological testing after emergence from anesthesia.RESULTS: Patients ranged in age from 6 to 16 years (mean age, 12.5 years). Propofol induced mild reductions in blood pressure (12.4% for systolic and 13.9% for diastolic blood pressure) and heart rate (mean reduction of 4.7%), which did not require specific treatment in any patient. Recovery from anesthesia was smooth and rapid, allowing initiation of Wada testing within 15 to 25 minutes of cessation of propofol. Wada testing was successfully accomplished in all patients.CONCLUSION: Propofol provided rapid induction of anesthesia, was administered without endotracheal intubation, and did not cause substantial changes in cardiorespiratory parameters. Propofol anesthesia allowed controlled angiography among patients as young as 6 years and did not interfere with neuropsychological testing.